Visions et obstacles de la différenciation pédagogique pour des enseignants secondaires débutants - Gremion François; Gremion Lise (Éducation et Socialisation)
Between the pedagogical ideal and the constraints, young secondary teachers who are new to the profession discuss, in a focus group, what pedagogical differentiation means to them. Their definitions are rooted in their everyday school life. They do not refer to an univocal model, but rather to an extension of their experience in the classroom, as well as to the obstacles already encountered in their practice, be it the overload of the early days in the profession, the need to assimilate into the habits of colleagues or the economy of effort on the part of pupils. This reality is actualized here in the singularity of each college.